Contribution to the study of the genus Paratylenchus Micoletzky, 1922 sensu lato (Nematoda: Tylenchulidae) - Ghaderi, Reza; Kashi, Leila; Karegar, Akbar (Zootaxa, 2014)
Morphological and morphometric analyses were conducted on the genus Paratylenchus, based on documented data in the literature and characters of Iranian populations of twelve species, including P. arculatus, P. colinus, P. conicephalus, P. coronatus, P. neoamblycephalus, P. neoprojectus, P. obtusicaudatus, P. paraperaticus, P. similis, P. straeleni, P. variabilis and P. veruculatus. Moreover, males of P. obtusicaudatus are described for the first time and additional data provided for males of P. paraperaticus. The variability of the most important taxonomic characters for species identification in the genus was estimated by calculation of coefficient of variation (CV) for 49 species and the ratio of extremes in the range of measured females (max/min ratios) for 82 species of the genus, based on 66 and 170 populations, respectively. A list of 117 valid species of Paratylenchus is provided, along with a dichotomous identification key and a diagnostic compendium.